2006
DOI: 10.1111/j.1471-4159.2006.04239.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the galanin receptor 2 (GalR2) protects the hippocampus from neuronal damage

Abstract: Expression of the neuropeptide galanin is up-regulated in many brain regions following nerve injury and in the basal forebrain of patients with Alzheimer's disease. We have previously demonstrated that galanin modulates hippocampal neuronal survival, although it was unclear which receptor subtype(s) mediates this effect. Here we report that the protective role played by galanin in hippocampal cultures is abolished in animals carrying a loss-of-function mutation in the second galanin receptor subtype (GalR2-MUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 45 publications
9
86
0
Order By: Relevance
“…Furthermore the addition of exogenous galanin peptide or the GalR2/3-specific agonist Gal2-11 reduced the amount of cell death when co-administered with either glutamate or staurosporine in WT primary hippocampal cultures (15). We have recently extended these findings by demonstrating that organotypic hippocampal cultures from mice with a loss-of-function mutation in GalR2 (GalR2-MUT) treated with glutamate show more cell death than WT controls and this cannot be rescued with the addition of either exogenous galanin or Gal2-11 (16). In support of these findings, studies by Pirondi and colleagues have shown that glutamate induced upregulation of c-fos can be reversed using galanin or Gal2-11 (17).…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Furthermore the addition of exogenous galanin peptide or the GalR2/3-specific agonist Gal2-11 reduced the amount of cell death when co-administered with either glutamate or staurosporine in WT primary hippocampal cultures (15). We have recently extended these findings by demonstrating that organotypic hippocampal cultures from mice with a loss-of-function mutation in GalR2 (GalR2-MUT) treated with glutamate show more cell death than WT controls and this cannot be rescued with the addition of either exogenous galanin or Gal2-11 (16). In support of these findings, studies by Pirondi and colleagues have shown that glutamate induced upregulation of c-fos can be reversed using galanin or Gal2-11 (17).…”
mentioning
confidence: 57%
“…All three subtypes are expressed by differing neuronal populations in the brain [reviewed in (30,31)], and in addition Su and colleagues have shown that GalR2 (but not GalR1 or GalR3) is expressed by rat primary microglia and the murine BV2 and rat HAPI glial clonal cell lines (32). Consistent with a neuroprotective role, GalR2 (unlike GalR1 or GalR3) is known to signal via G q/11 to activate phospholipase C and protein kinase C (33,34) and hence ERK (16). Previous studies have also shown that hippocampal neuroprotection is dependent in part upon activation of ERK (35,36) and ERK KO mice have increased susceptibility to EAE (37).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Activation of GAL 2 is capable of stimulating the MAPK/ ERK pathway in a PTX-sensitive, PKC-dependent fashion, indicative of coupling to a G 0 protein in GAL 2 -transfected cell lines (Wang et al, 1998c). Endogenous GAL 2 -induced activation of the MAPK/ERK pathway via PKC has been reported in rodent hippocampal neurons (Hawes et al, 2006;Elliott-Hunt et al, 2007), rat microglial cells (Ifuku et al, 2011), rat PC12 pheochromocytoma cells (Hawes et al, 2006), and human small-cell lung cancer (SCLC) cells (Seufferlein and Rozengurt, 1996), although in the latter, MAPK/ ERK pathway activation can also occur independently of PKC (Wittau et al, 2000). GAL 2 predominantly couples to a G q/11 -type G protein, leading to phospholipase C activation, which stimulates Ca 2+ release via inositol phosphate hydrolysis and opens Ca 2+ -dependent ion channels in a PTXresistant manner, in both GAL 2 -transfected cell lines (Smith et al, 1997b;Borowsky et al, 1998;Fathi et al, 1998;Pang et al, 1998;Wang et al, 1998c) and GAL 2 -expressing rat microglial cells (Ifuku et al, 2011).…”
Section: B Galanin Receptor Signalingmentioning
confidence: 99%
“…Thus, in many models of intestinal pathology galanin content and the number of GAL-Ir neurons may be altered suggesting the adaptive possibilities of the enteric neurons. This may be associated with the neuroprotective action of galanin that was well-documented in many experimental models of brain, nerve and neurons' injury [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%